Investigating the Impact of the Air Void Charges on the Surface Electric Field Distribution of the GIS Spacer - Awad, Ahmed; Saleh, Dawood (Iraqi Journal for Electrical and Electronic Engineering, 2025)
One of the important components of the gas-insulated switchgear (GIS) system are spacers. These insulators are not free from some manufacturing and operational defects that adversely affect their performance, and among these defects is the presence of air voids inside the solid insulator, which may be exposed to high electric fields that may lead to partial discharges within the voids. These partial discharges may cause the accumulation of charges on the surfaces of these insulators, increase the concentration of the electric field, and cause electric flashover across the interface surfaces between the SF6 gas and the solid insulator. With a 2D axisymmetric model based on finite element analysis (FEA) implemented in COMSOL Multiphysics software, this study investigates the impact of the charges that accumulated on the inner surfaces of the void on the electric field distribution of the spacer’s interior and exterior surfaces, as their effect is investigated when they are in different size and locations inside the insulator. This effect is more noticeable when the density of charges on the inner surface of the void increases to 1 (μC/m2) and the radius is 2 mm. When the void positioned 1 mm from both the inner and outer surfaces of the spacer, the electric field values are 14.55 and 9.4 MV/m, respectively. The impact site on the spacer surface is narrow within 3 mm and depends on the size of the void. The field enhancement factor may reach 2, and its value is higher on the outer surface than on the inner surface.